PERANCANGAN SISTEM INFORMASI SISTEM PRODUKSI PERUSAHAAN SEKTOR TEH MENGGUNAKAN SOFTWARE “STARUML” - Ahmad Ripai; M. Reza Syahputra, Anang Khoiri Najib, Putra Adriansyah, Raja Dewa Wisnu (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Various industries, including the tea industry, have been greatly affected by advances in information technology. By using StarUML software, this research aims to create an effective production information system for companies in the tea industry. The system design methods used include requirements analysis, database design, and system modeling using activity diagrams, use cases, and Class diagrams. System modeling with StarUML helps to visualize the production process visually and logically. A case study was conducted on a local tea company to assess the needs of their production information system. The results of this analysis are used to create a normalized database with Microsoft Access. Data normalization is carried out to guarantee an ideal data structure and reduce data redundancy. In system modeling, StarUML enables the visualization of use case diagrams to show the interaction between actors and systems. In addition, Class diagrams can show Class relationships and Class hierarchies. This study found that the use of StarUML as a tool in designing production information systems can improve the operational efficiency of companies in the tea industry. It is expected that the planned implementation of the information system will improve the control and supervision of the production process, as well as make it easier for management to make decisions.